2012
DOI: 10.1890/11-1740.1
|View full text |Cite
|
Sign up to set email alerts
|

Invasive ecosystem engineer selects for different phenotypes of an associated native species

Abstract: Abstract. Invasive habitat-forming ecosystem engineers modify the abiotic environment and thus represent a major perturbation to many ecosystems. Because native species often persist in these invaded habitats but have no shared history with the ecosystem engineer, the engineer may impose novel selective pressure on native species. In this study, we used a phenotypic selection framework to determine whether an invasive habitat-forming ecosystem engineer (the seaweed Caulerpa taxifolia) selects for different phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Recent research on the reciprocal interactions between ecological and evolutionary dynamics is increasingly filling this gap (Hairston et al 2005, Schoener 2011, Becks et al 2012), but more studies are needed that examine how chemical modifications of the environment by organisms affect the evolution of consumer resource demand (Mizuno andKawata 2009, Matthews et al 2011b), and how physical modification of the environment by ecosystem engineers can modify selection gradients of the engineers themselves or of other organisms (Wright et al 2012). …”
Section: See Criteria Column)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research on the reciprocal interactions between ecological and evolutionary dynamics is increasingly filling this gap (Hairston et al 2005, Schoener 2011, Becks et al 2012), but more studies are needed that examine how chemical modifications of the environment by organisms affect the evolution of consumer resource demand (Mizuno andKawata 2009, Matthews et al 2011b), and how physical modification of the environment by ecosystem engineers can modify selection gradients of the engineers themselves or of other organisms (Wright et al 2012). …”
Section: See Criteria Column)mentioning
confidence: 99%
“…However, there is little experimental evidence showing how bioturbation activities can affect selection pressures (Criterion 2) in a way that would affect evolutionary responses (Criterion 3). There are, however, experimental studies that measure changes in selection pressures caused by organism-mediated modifications to the environment, illustrative of the type of research needed to address the second criterion (Wright et al 2012). In a study on ecosystem engineers, Wright et al (2012) showed that invasive seaweeds (Caulerpa taxifolia) modify the physical and chemical characteristics of coastal marine sediments, and, in so doing, alter selection gradients on native bivalves (Anadara trapezia).…”
Section: Experimentally Test More Putative Mechanisms Of Niche Constrmentioning
confidence: 99%
See 1 more Smart Citation
“…Shell length was used as a measure of body size as morphological traits (e.g. length, width, height, total weight) are highly correlated in marine molluscs such as A. trapezia (Wright & Gribben 2008, Gribben et al 2009a, Wright et al 2012.…”
Section: Data Collectionmentioning
confidence: 99%
“…Shell length was used as a measure of body size as morphological traits (e.g. length, width, height, total weight) are highly correlated in marine molluscs such as A. trapezia (Wright & Gribben 2008, Gribben et al 2009a, Wright et al 2012.To investigate the effects of abiotic variation on the abundance and body size of Anadara trapezia and Batillaria australis, water temperature, pH, salinity, dissolved oxygen (DO) and sediment redox (a proxy for general sediment health) (Gribben et al 2009b, McKinnon et al 2009, Wright et al 2010 were measured in all habitats at all sites. All these abiotic variables can have important effects on marine invertebrates (Rainer et al 1979, Berge et al 2006, Harley et al 2006, Bibby et al 2007, Gribben et al 2009b, McKinnon et al 2009, Wright et al 2010.…”
mentioning
confidence: 99%